Familial Twinning and Fertility in Dutch Mothers of Twins - Hoekstra, Chantal (2008)
We studied twinning and fertility indices in mothers with spontaneous monozygotic (MZ) and dizygotic (DZ) twins and in mothers who conceived their twins after the use of assisted reproduction techniques (ART). Participants in this study consisted of 8,222 and 5,505 women with spontaneous DZ and MZ offspring and 4,164 and 250 women with ART DZ and MZ twin pairs, respectively. Women were compared with respect to the number of sibs and offspring, the presence of other relatives with twins and the time it took to conceive the twins. We also compared familial twinning between a younger and an older age group. Women with spontaneous DZ twins more often reported female relatives with twins than those with spontaneous MZ twins. The proportion of DZ versus MZ twin offspring in relatives was also larger in women with spontaneous DZ offspring than in women with MZ offspring. The first group of women reported a shorter time to conceive. Women with ART twins had fewer sibs and offspring and less often reported relatives with twins. We did not observe that DZ twinning was more familial in women who had their twins before age 36 years compared to older women. Familial DZ twinning is clearly present in mothers of spontaneous DZ twins. The mechanisms underlying spontaneous and non-spontaneous DZ twinning are different and fertility treatment should be taken into account in any study of twinning. Twinning is not more familial in women who have their twins at a younger age.